Roles and challenges for Muslim women in the restive southern border provinces of Thailand (Justice for Peace Foundation, 2010)
Report was presented on the 'Conference on religious activism and women's development in Southeast Asia : highlighting impediments, exploring opportunities (20-21 November 2009)